Neprilysin, obesity and the metabolic syndrome - Standeven, Kristina F. (2010)
OBJECTIVE: Neprilysin (NEP), a zinc metallo-endopeptidase, has a role in blood pressure control and lipid metabolism. The present study tested the hypothesis that NEP is associated with insulin resistance and features of the metabolic syndrome (MetS) in a study of 318 healthy human subjects and in murine obesity and investigated NEP production by adipocytes in-vitro. METHODS AND RESULTS: In 318 white European males, plasma NEP was elevated in the MetS and increased progressively with increasing MetS components. Plasma NEP activity correlated with insulin, homeostasis model assessment and body mass index in all subjects (p<0.01). Quantitative RT-PCR and Western blotting showed that in human pre-adipocytes NEP expression is upregulated 25-30 fold during differentiation into adipocytes. Microarray analysis of mRNA from differentiated human adipocytes confirmed high NEP expression comparable to adiponectin and plasminogen activator inhibitor-1. In a murine model of diet-induced insulin resistance, plasma NEP levels were significantly higher in high fat diet (HFD)-fed compared with normal chow diet (NCD)-fed animals (1642±529 and 820±487 pg/μl, respectively; p<0.01). Tissue NEP was increased in mesenteric fat in HFD compared with NCD-fed mice (p<0.05). NEP knock out mice did not display any changes in insulin resistance, glucose tolerance or body and epididymal fat pad weight compared to wild type mice. CONCLUSIONS: In humans, NEP activity correlated with body mass index and measures of insulin resistance with increasing levels in subjects with multiple cardiovascular risk factors. NEP protein production in human adipocytes increased during cell differentiation and plasma and adipose tissue levels of NEP were increased in obese insulin resistant mice. Our results indicate that NEP associates with cardio-metabolic risk in the presence of insulin resistance and increases in obesity.